2021
DOI: 10.1177/14680874211043390
|View full text |Cite
|
Sign up to set email alerts
|

Limits of compression ratio in spark-ignition combustion with methanol

Abstract: A shift toward a circular and [Formula: see text]-neutral world is required, in which rapid defossilization and lower emissions are realized. A promising alternative fuel that has gained traction is methanol, thanks to its favorable and clean-burning fuel properties as well as its ability to be produced in a carbon-neutral process. Especially methanol’s high knock resistance and its combustion stability offer the opportunity to operate an engine at both a high compression ratio and a high excess air dilution. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The experimental investigations were carried out on a four stroke DI SI single-cylinder research engine (SCE) with a displacement in the range of those for passenger car applications. 10,11 The SCE is modularly designed and capable of operating with different cylinder heads, pistons, compression ratios, and injection and combustion strategies. In the present work, a cylinder head capable of combustion concepts with both PC and SI was used.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental investigations were carried out on a four stroke DI SI single-cylinder research engine (SCE) with a displacement in the range of those for passenger car applications. 10,11 The SCE is modularly designed and capable of operating with different cylinder heads, pistons, compression ratios, and injection and combustion strategies. In the present work, a cylinder head capable of combustion concepts with both PC and SI was used.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, for every measurement 200 consecutive engine cycles were measured and statistical measures applied to analyze the combustion. Test bench data, static pressures and temperatures were adjusted and mass flows were measured according to Wouters et al 30 The calculation of the indicated efficiency is performed automatically at the test bench by the automation system of the engine and checked during post-processing of the data. The formula including a uncertainty analysis can be found in Appendix B.…”
Section: Single-cylinder Enginementioning
confidence: 99%
“…These results are in good agreement with earlier investigations. [5][6][7] Thus, if ultra-lean engine operation is targeted with new combustion concepts, 8 which could be further extended with alternative fuels, 9 then solutions must be found to mitigate the increasing hydrocarbon emissions according to achieve future emission limits. 10 This applies in particular to the higher alkane emissions at lean engine operation conditions.…”
Section: Introductionmentioning
confidence: 99%